Novel Indication for Chimney Graft Placement in the Inferior Mesenteric Artery in AAA Patients with Coexistent Bilateral Internal Iliac Artery Occlusion. (August 2014) - Donas, Konstantinos P.; Torsello, Giovanni; Bisdas, Theodosios; Austermann, Martin; Stavroulakis, Konstantinos; Pitoulias, Georgios A.
Purpose: To report a novel indication for the use of chimney grafts to preserve flow to the inferior mesenteric artery (IMA) in patients undergoing endovascular aneurysm repair (EVAR) for aortobi-iliac aneurysms with coexistent bilateral occlusion of the internal iliac arteries (IIA). Technique: Via a cutdown over the left axillary artery, a 5-F vertebral catheter was delivered over a conventional 0.035-inch hydrophilic guidewire to selectively catheterize the IMA via a 7-F shuttle sheath, which was then advanced at least 2 cm into the target vessel. The first chimney graft was advanced into the sheath, and a standard EVAR procedure followed. The chimney graft was deployed at least 2 cm in the IMA; a second chimney graft was advanced and deployed with at least 2 cm overlapping with the first chimney stent parallel and outside of the main abdominal endograft and below the lowest renal artery. The chimney grafts were lined with additional bare nitinol stents. The technique is demonstrated in two male patients who suffered from symptomatic aortobi-iliac aneurysm with patent IMAs and bilateral IIA occlusion. The procedure was completed successfully in both cases without bowel ischemia. At 12 and 6 months, respectively, the chimney grafts remained patent without endoleak. The patients are asymptomatic. Conclusion: The IMA chimney endovascular technique can be considered in EVAR cases with coexistent bilateral IIA occlusion to minimize the risk for bowel ischemia.